Corrosion behavior of electron beam processed AZ91 magnesium alloy - Fatemeh Iranshahi; Mohammad Bagher Nasiri; Fernando Gustavo Warchomicka; Christof Sommitsch (Journal of Magnesium and Alloys, 2020)
The increasing use of light alloys owing to their high performance makes magnesium alloys very attractive for the use in automotive and biomedical applications. However, it is well known that magnesium and its alloys have poor corrosion resistance in different atmospheric and aqueous environments. As a means of improving corrosion resistance through the microstructure modification, electron beam processing (EBP) was applied on the as-cast AZ91 magnesium alloy. To evaluate the microstructure influence on the corrosion-resistant, the EB processed samples underwent a solution heat treatment and an artificial aging heat treatment. Four different obtained microstructures were investigated by standard microscopy and electrochemical corrosion tests to evaluate the microstructure and its effects on the corrosion resistance of AZ91 alloy. The EBPed specimens show a significant microstructure refinement and homogenous distribution of β-phase at the grain boundaries surrounded by supersaturated α-Mg which acts as a barrier against corrosion. The electrochemical corrosion test of the samples immersed in 3.5 wt% NaCl after 4 weeks indicates that the EBP improves the corrosion resistance of the alloy due to the nobler corrosion potential of supersaturated α-Mg and more stable protective hydroxide films compared to the heat-treated and as-cast conditions.